2021
DOI: 10.1016/j.ijrobp.2021.04.029
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawn: Low dose radiation therapy for severe COVID-19 pneumonia: a randomized double-blind study

Abstract: Purpose The morbidity and mortality of patients requiring mechanical ventilation for coronavirus disease 2019 (COVID-19) pneumonia is considerable. We studied the use of whole-lung low dose radiation therapy (LDRT) in this patient cohort. Methods and Materials : Patients admitted to the intensive care unit (ICU) and requiring mechanical ventilation for COVID-19 pneumonia were included in this randomized double-blind study. Patients were randomized to 1 Gy whole-lung LDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Beyond the technique used for LD-RT, also debatable because it is far from the quality standards required by modern radiotherapy, the results of the study did not demonstrate the benefit of LD-RT in improving the situation of critically ill patients in the ICU, therefore advising against its use. However, as the authors themselves acknowledge, one of the reasons that could justify the lack of benefit lies in the selection of patients, with an extremely critical condition requiring constant mechanical ventilation [ 29 ]. Probably, like it has been previously commented, LD-RT should be considered in the initial phases of the exacerbated inflammatory response that accompanies the SARS-CoV‑2 infection, the so-called ‘cytokine storm’, in order to maximize the anti-inflammatory effect of dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the technique used for LD-RT, also debatable because it is far from the quality standards required by modern radiotherapy, the results of the study did not demonstrate the benefit of LD-RT in improving the situation of critically ill patients in the ICU, therefore advising against its use. However, as the authors themselves acknowledge, one of the reasons that could justify the lack of benefit lies in the selection of patients, with an extremely critical condition requiring constant mechanical ventilation [ 29 ]. Probably, like it has been previously commented, LD-RT should be considered in the initial phases of the exacerbated inflammatory response that accompanies the SARS-CoV‑2 infection, the so-called ‘cytokine storm’, in order to maximize the anti-inflammatory effect of dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…However few studies such as that of Papachristofilou et al. demonstrated no benefit of LDRT to improve recovery in critically ill patients requiring MV for COVID-19 pneumonia ( 23 ). Available studies have also indicated the importance of the timing of LDRT to bilateral lung fields stating that there is a small window of opportunity after which radiation may not be adequately effective.…”
Section: Discussionmentioning
confidence: 99%